High-Quality Web Information Provisioning and Quality-Based Data Pricing - Stahl, Florian (TESTINSTANZ: Wissenschaftliche Schriften der Universität Münster, 2016)
Today, information can be considered a production factor. This is attributed to the technological innovations the Internet and the Web have brought about. Now, a plethora of information is available making it hard to find the most relevant information. Subsequently, the issue of finding and purchasing high-quality data arises. Addressing these challenges, this work first examines how high-quality information provisioning can be achieved with an approach called WiPo that exploits the idea of curation, i. e., the selection, organisation, and provisioning of information with human involvement. The second part of this work investigates the issue that there is little understanding of what the value of data is and how it can be priced – despite the fact that it is already being traded on data marketplaces. To overcome this, a pricing approach based on the Multiple-Choice Knapsack Problem is proposed that allows for utility maximisation for customers and profit maximisation for vendors. Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-67249643318 ISBN978-3-8405-0133-3 Paperback, XIII, 296 Seiten